Pragmatic Analysis: Racism in Crazy Rich Asians Movie (2018) - Aprilia Intan Permata Sari (Fakultas Ilmu Budaya, 2024)
This thesis discusses Racism in Crazy Rich Asians Movie (2018). This research is aimed to examine the existence of racist discriminatory pratice that causes racial inequality in the movie. Since the study focuses on the linguistics element carried in the movie, speech act by Austin (1962) and Searle (1979) is used as a tool to analyze the action carried in the locution uttered by the Asian and Asian-American characters in the movie. Besides, some supporting concepts of racism by Van Dijk (1993b, 1993c, 2000b) also used to connect the result of analysis to the social issue brought in the movie with the related issue in real life. This research is descriptive qualitative research. The source of the data of this research is Crazy Rich Asians Movie subtitle. The utterances in the movie were based on racist features proposed by Van Dijk (1993b, 1993c, 2000b). Hence, the data are in the form of racist utterances. The result of the analysis shows that assertives and directives are the dominant types of illocutionary force produced by the Asian characters and followed by expressives and declaratives produced by the Asian-American character. Those illocutionary forces have been identified to carry some forms of racist discriminatory practices. Firstly, exclution act is carried in assertives, directives and declaratives illocutonary force which aimed to prevent the minority group to involve in some activities. Secondly, marginalization acts are found in assertives and directives illocuitonary forces that aimed to keep the Asian – American character in a lower position. thirdly, inferiorization occurs in expressives illocutionary forces that is aimed to treat the Asian-American character as inferior than Asian characters in the movie. Last, derogation that aimed to insult the minority character, found in assertives illocuitonary force.
Entry oleh Arif 2026 Maret 26
Keywords: Racism; Crazy Rich Asians Movie (2018)